2021
DOI: 10.3390/su14010443
|View full text |Cite
|
Sign up to set email alerts
|

How Do Stakeholder Pressures Affect Corporate Social Responsibility Adoption? Evidence from Chinese Manufacturing Enterprises in Ethiopia

Abstract: In today’s globalized world, one of the great challenges for enterprises is integrating CSR adoption into their operations. The study aims to investigate how stakeholder pressure influences the adoption of corporate social responsibility (CSR) practices by Chinese medium and large-scale manufacturing enterprises in Ethiopia. This study used a mixed-methods research approach that includes primary and secondary data sources. The employed research data were analyzed using stakeholder theory, structural equation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 85 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…The attention given to stakeholders by policymakers is said to depend on factors such as legitimacy, urgency, power, interest, organisational culture, motivation, the mindset of the stakeholder, stakeholder capacity, and organisational leadership. These factors have been discussed in previous studies (Aaltonen & Kujala, 2010;Ackermann & Eden, 2011;Jones, Felps, & Bigley, 2007;Squires et al, 2022;Windsor, 2010;Wosahlo, 2014;Ying, Shan, & Tikuye, 2022). However, this study argues that the anti-violence against women and children policy process is affected by factors such as legitimacy, urgency, power, interest, social norms, awareness, and stakeholder capacity.…”
Section: Regional Technical Implementation Unit For the Protection Of...mentioning
confidence: 76%
“…The attention given to stakeholders by policymakers is said to depend on factors such as legitimacy, urgency, power, interest, organisational culture, motivation, the mindset of the stakeholder, stakeholder capacity, and organisational leadership. These factors have been discussed in previous studies (Aaltonen & Kujala, 2010;Ackermann & Eden, 2011;Jones, Felps, & Bigley, 2007;Squires et al, 2022;Windsor, 2010;Wosahlo, 2014;Ying, Shan, & Tikuye, 2022). However, this study argues that the anti-violence against women and children policy process is affected by factors such as legitimacy, urgency, power, interest, social norms, awareness, and stakeholder capacity.…”
Section: Regional Technical Implementation Unit For the Protection Of...mentioning
confidence: 76%
“…Cho et al, 2019). Research conducted by Ying, (2022) found that stakeholder pressure influences corporate CSR adoption in China. Mawardi (2019) in his research stated that there are two stakeholder groups that play a very important role in supporting CSR activities which will ultimately affect financial performance, namely customer groups and employee groups.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Green behavior was largely discussed in the literature on corporate performance [26][27][28][29][30][31], social responsibility, and corporate sustainability [32][33][34][35]. Green actions include green product design [36,37], green production management [38][39][40], green brand promotion [41][42][43], and so on.…”
Section: Informative Publicity and Corporate Behaviormentioning
confidence: 99%